Georgia Architectural and Historic Properties Survey of 606 River St., Valdosta, Ga., December 1980 - Smith, Bartholomew; Bartholomew, Beth (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 606 River St., Valdosta, Ga., December 1980. 1 story rectangular shiplap sided house with multi-gabled tin roof. Gabled porch with square posts. Double hung sash windows with 2/2 lights. Set on brick piers. Fair condition. Date of Construction: Prior to 1922. Functional house in area settled by middle class. Significant as part of a potential N.R. district.
Georgia Architectural and Historic Properties Survey of 606 River St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 78.7 MB (82,536,823 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)